Pengaruh Media Poster terhadap Pengetahuan dan Sikap tentang Kesehatan Mental pada Remaja di SMAN 5 Kota Jambi - Magda Carrina Aurora; Ismi Nurwaqiah Ibnu; Vinna Rahayu Ningsih (Pusat riset dan Inovasi Nasional, 2025)
Mental health is a condition in which a person is free from all symptoms of mental disorders. Anxiety disorder is the most common mental disorder experienced by adolescents and depression reaches 26.7%. The purpose of this study was to determine the knowledge and attitudes of adolescents through poster media both before and after interventions related to mental health. The type of research used is quantitative with one group pre-test post-test method, with intervention using poster media and questionnaires as data collection tools at SMAN 5 Jambi City. The sample in this study amounted to 30 respondents and was tested using the Paired T-Test statistical test. The pre-test results showed that the percentage of knowledge before the intervention was 66.7% to 100% after the intervention and the percentage of attitude before the intervention was 76.7% to 96.7%. After the intervention on mental health, there was an increase in knowledge with P-Value = <.001 and an increase in attitude with P-Value = <.001. This study shows that there is an influence on knowledge and attitudes before and after the intervention of poster media on mental health at SMAN 5 Jambi City. It is recommended to hold interactive discussions with counseling teachers in schools aimed at increasing adolescents' understanding of mental health and being able to reduce the stigma of the surrounding environment so that students do not feel afraid or embarrassed to seek help.